Pengembangan Kurikulum Berbasis Keterampilan Abad ke-21: Perspektif dan Tantangan - Heriman, Muhammad; Dede Atung; Endang Sutisna; Nia Nurhayati; Ika Kartika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Education in the 21st century is faced with demands to prepare students with skills that are relevant to the dynamics of society and the ever-evolving world of work. Developing a 21st century skills-based curriculum is a must to ensure that graduates not only have academic knowledge, but also the skills necessary to succeed in an era marked by the Industrial Revolution 4.0. This paper explains perspectives in developing a 21st century skills-based curriculum, outlining critical aspects such as critical thinking skills, creativity, effective communication, and collaboration. This perspective addresses the urgent need to integrate 21st century skills into the curriculum, creating relevant and contextual learning experiences. However, the implementation process is not free from a number of challenges that require serious attention. These challenges involve paradigm shifts in teaching and learning approaches, adjustments to assessment methods, and increased stakeholder involvement. In addition, this article also provides an overview of how teachers can develop their skills through a professional development approach that focuses on the needs of a 21st century skills-based curriculum. Through a deep understanding of these perspectives and challenges, it is hoped that we can design effective solutions that can be implemented at various levels of education.